2016 13th IEEE Annual Consumer Communications &Amp; Networking Conference (CCNC) 2016
DOI: 10.1109/ccnc.2016.7444946
|View full text |Cite
|
Sign up to set email alerts
|

Personalizing Pedestrian Accessible way-finding with mPASS

Abstract: This work presents users evaluation of mPASS (mobile Pervasive Accessibility Social Sensing), a system to provide citizens with personalized accessible way finding. mPASS collects data both from crowdsourcing and from crowdsensing, in order to obtain a detailed georeferenced description of the urban environment accessibility. It combines these data with a user profile, with the aim of tailoring paths and maps to users' preferences and needs. To drive the design of our application, we assessed our first proposa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(21 citation statements)
references
References 20 publications
1
20
0
Order By: Relevance
“…For instance, in one of the early works, Prandi et al, [10] explored the potentials of the crowdsourcing communities in improving data access and services in the field of disable pedestrian mobility. Similar works have been followed by [11][12][13][14][15][16][17][18][19]. Among those, mPASS [19] presents a valuable mobile pervasive accessibility social sensing framework.…”
Section: Introductionmentioning
confidence: 84%
“…For instance, in one of the early works, Prandi et al, [10] explored the potentials of the crowdsourcing communities in improving data access and services in the field of disable pedestrian mobility. Similar works have been followed by [11][12][13][14][15][16][17][18][19]. Among those, mPASS [19] presents a valuable mobile pervasive accessibility social sensing framework.…”
Section: Introductionmentioning
confidence: 84%
“…WEMAP [16] intends to improve these offers, generating door-to-door routes, using crowdsourcing data and information from local businesses' websites. mPASS system [50], WheelShare [51], and Wegoto [52] collect crowdsensing data, taking advantage of the sensory and computational resources of smartphones. When users are on the move, the data provided by accelerometers and gyroscopes is related to their physical location using GPS.…”
Section: Related Workmentioning
confidence: 99%
“…Recently, scholars have discovered that distance is not the only factor that humans take into consideration when preferring a route over another [17][18][19]. In fact, some studies have suggested that some individuals may even deviate up to approximately a 30% from the shortest path in exchange for a pleasant journey [20]. The factors that may influence the users' decisions are varied.…”
Section: Related Workmentioning
confidence: 99%